Audit Keamanan Sistem Informasi Menggunakan Cobit 5 di PT. Paramita Surya Makmur Plastika - Titan Parama Yoga Titan; R. Yadi Rakhman Alamsyah; Silca Silkillah Adwa (Jurnal Accounting Information System (AIMS), 2023)
One of the main problems for a company is information system security. High security is needed to maintain the confidentiality and misuse of information in the organization. To improve the security of business operations and the quality of information technology resources, it is necessary to evaluate to optimize the security of existing information technology assets. The purpose of this research is to carry out an information system security audit at PT. Paramita Surya Makmur Plastika using COBIT 5 and documenting the information system audit findings of PT. Paramita Surya Makmur Plastika to produce an audit report. Based on the results of research that has been carried out through interviews and questionnaires using COBIT 5 and using the APO13 and DSS05 sub domains, the results show that the existing capability is at level 1 while the expected capability level is at level 3 andt the capability gap is 2.